Vietnam : Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility - Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by Authorities of Vietnam. (IMF Staff Country Reports; Country Report ;, 2001)
Vietnam's economic recovery from the spillover effects of the Asian crisis has continued and the pace of policy reform has stepped up. The government's program seeks to build on this record and policy momentum. A cautious fiscal stance will ensure a sustainable public debt burden. The liberalization of the exchange regime and improving the business environment will be essential to restore investor confidence. Attaining the objectives of the program will hinge on the close coordination of credit policy with state-owned commercial bank (SOCB) reform.